Cardiovascular changes in women with computerized bicycle training - Slavin, Sharon (My University, 1988)
Thirty-four sedentary women with a mean age of 32 years were studied to determine the extent to which training effects would occur after a six-week computerized bicycle exercise program. In addition, training differences between 12- and 24-minute computerized protocols were examined. Subjects were divided into five groups: controls (C, n=10); program-12 (P-12, n=8); random-12 (R-12, n=4); program-24 (P-24, n=8); random-24 (R-24, n=4). All subjects received pre-training maximal bicycle testing, six-weeks of training (3 days wk -1), and post-training maximal testing. A 7.9% increase was found in V02max (ml kgBW -1 min -1) after training which was accompanied by a 15.0% increase in total ride time on the bicycle test. Although these changes approached significance and subjects reported that the workloads seemed easier after training (RPE = 16.71 + 5.27), none of the comparisons were found to be significant. Small group sizes, large standard deviations and low intensity levels for training contributed to the lack of significance. Protocol comparisons revealed a non-significant tendency for the programmed protocols to increase VO2max more (9.8% and 9.2%) than the random protocols (5.2% for both groups). It was concluded that computerized bicycle training is probably a suitable means of cardiovascular training for women when it is performed longer than six-weeks.
Keywords: Cardiovascular system; Cycling -- Physiological aspects